2013
DOI: 10.1177/0017896913485742
|View full text |Cite
|
Sign up to set email alerts
|

Teacher satisfaction with school and psychological well-being affects their readiness to help children with mental health problems

Abstract: Objective: In support of a whole-school approach to mental health promotion, this study was conducted to find out whether and how significantly teachers' satisfaction with school and their subjective psychological well-being are related to the belief that they can help pupils with mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 39 publications
4
82
0
7
Order By: Relevance
“…This decrease in 'good will', reluctance to help and withdrawal from extracurricular support have been reported in other surveys, 37 and emphasize how teachers' ability to support the mental health needs of pupils may be compromised by their own mental health status. 34,35 This disintegration of the teacher/pupil relationship may serve to consolidate a young person's reluctance to seek help, confirming their fear of stigma and preconceptions about an adult's ability to fully understand their adolescent problems. 12 These findings stand in stark contrast to the local and international expectations of how teachers should be at the frontline in early identification and support for the mental health of their students.…”
Section: The Impact Of Teacher Stressmentioning
confidence: 96%
See 2 more Smart Citations
“…This decrease in 'good will', reluctance to help and withdrawal from extracurricular support have been reported in other surveys, 37 and emphasize how teachers' ability to support the mental health needs of pupils may be compromised by their own mental health status. 34,35 This disintegration of the teacher/pupil relationship may serve to consolidate a young person's reluctance to seek help, confirming their fear of stigma and preconceptions about an adult's ability to fully understand their adolescent problems. 12 These findings stand in stark contrast to the local and international expectations of how teachers should be at the frontline in early identification and support for the mental health of their students.…”
Section: The Impact Of Teacher Stressmentioning
confidence: 96%
“…36 Job satisfaction, psychological well-being and a positive teacher/pupil relationship are key factors which will determine the likelihood that a teacher will want to support, and have the emotional resources, with which to help their students. 26,34 The qualitative component of our survey, while limited, has provided a glimpse of such issues, with a handful of teachers revealing that they are unwilling to take on extra responsibilities or get involved in interactions with pupils because of their own high stress levels and lack of emotional well-being. Indeed, one teacher reported actively avoiding pupils and additional duties and described their growing impatience with students who needed extra emotional support from them.…”
Section: The Impact Of Teacher Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of educational settings in enhancing SWB within the taught elements of the curriculum is well evidenced (Brooks, 2013). In recent decades, an increasing body of evidence has indicated that the most effective programmes adopt a whole-school approach, that not only focus on taught components but encompass a more synergistic approach to the domains of the child outside of school, notably family and community as well as embedding a positive culture within the school that promotes pupil and staff well-being (Sisask et al, 2013).The relationships between all members of the school community are also seen to have a significant influence on pupil outcomes including their levels of SWB (Suldo et al, 2006). School connectedness, defined as the result of an academic environment in which students believe that adults in the school care about their learning and about them as individuals (Blum and Libbey, 2004), has been seen to have a key role in determining the school as a health asset.…”
Section: Introductionmentioning
confidence: 99%
“…Sutton & Wheatley, 2003), well-being (e.g. Bakker, 2005, Sisask et al, 2014, academic achievement (e.g. Briner & Dewberry, 2007;Duckworth, Quinn, & Seligman, 2009), and supportive classroom climate and teacher-student relationships (e.g.…”
Section: Introductionmentioning
confidence: 99%